Dihydroartemisinin attenuates autoimmune thyroiditis by inhibiting the CXCR3/PI3K/AKT/NF-κB signaling pathway - Liu, Huijuan (Oncotarget, 2017)
Dihydroartemisinin (DHA) is the first generation of naturally occurring artemisinin derivatives with antimalarial activity. Recent research showed that this drug also features immunosuppressive and anti-inflammatory properties. Autoimmune thyroiditis (AIT) is a common organ-specific autoimmune disease with no available effective drug treatment. In this study, we investigated effects of DHA on AIT in vitro and in vivo. Results showed that DHA can visibly reduce antithyroglobulin antibody and thyroid peroxidase antibody levels and regulate T helper cells (Th) 1/Th2 imbalance of experimental AIT mice. DHA also dose-dependently suppressed proliferation of lymphocytes induced by lipopolysaccharide and concanavalin A. DHA inhibited binding of C-X-C chemokine ligand 10 (CXCL10) and its receptor (C–X–C motif) receptor 3 (CXCR3), thus inhibiting calcium flow. DHA can also reduce expression levels of PI3-kinase (PI3K), p-PI3K, protein kinase B (AKT), p-AKT, nuclear factor (NF)-κB/p65, and p-NF-κB/p65. In conclusion, DHA may serve as treatment drug for AIT by inhibiting the CXCR3/PI3K/AKT/NF-kB signaling pathway.